EFFORTS TO INCREASE READING INTEREST IN ELEMENTARY SCHOOLS - Siti Humairoh (Green Publisher, 2022)
This study aims to find alternatives to increase students' interest in reading, especially among elementary schools. Interest in reading is a big influence for students. Efforts to increase elementary school students' interest in reading are a shared responsibility, between the students themselves, teachers and parents. However, the low reading interest of students in elementary schools is one of the obstacles, the lack of desire and willingness from the students themselves, the teacher also does not require students to read books when learning is being taught to students. In an effort to increase elementary school students' interest in reading, students should be given support so that interest in reading emerges from students and is introduced to reading material so that students are accustomed to reading, therefore the reading habits of students when they are in elementary school will foster a high interest in reading. students grow up. This research was conducted by formulating a research problem looking for references from relevant and similar journals to analyze the data, journals were collected by searching the internet through Google Chendikia and/or Google Scholar. The data obtained were analyzed and compared with this research method using a descriptive research type with a quantitative approach. The results of the analysis can increase elementary school students' interest in reading.